Characterising "Green Building" as a topic in Twitter. Issue 4 (7th October 2019) - Palmer, Stuart; Udawatta, Nilupa
Abstract : Purpose: Sustainable construction is widely considered to be the best practice in construction, helping to create a healthy built environment. Social media is identified as a valuable data source for research on sustainable construction, and Twitter is a popular social media platform in relation to the construction. Green Building construction is identified as one of the methods that promotes sustainable construction. The purpose of this study is to characterise "Green Building" as a topic in Twitter. Design/methodology/approach: Social network analysis methods were applied to a large set of Twitter data related to "green building". Time sequence analysis and network visualisation were used to characterise Twitter activity and to identify influential users. Text analytics and visualisation methods were applied to the same data set to visualise the text content of Twitter posts relating to green building. Findings: Peaks in Twitter activity were associated with physical "green building" events. The network visualisation of the Twitter data revealed a complex structure and a range of types of interactions. The most "influential" users depended on the ranking method used; however, a number of users had high influence in all measures used. The tweet text visualisation showed evidence of a global and interactive audience on Twitter engaged in conversations about green building. Also, it was found that external links, emoji and popular terms related to a particular topic can be used to increase the engagement of Twitter users on that topic. Originality/value: Certain Green Building events were observed to be associated with high levels of Twitter activity. The virtual was found to be closely linked to the physical, and for the promotion of green building construction, their respective impact is potentially the most powerful when used in conjunction. The most influential Twitter accounts did not belong to one class of user, including both individuals and organisations. Twitter offers a platform for a range of stakeholders in the area of green building construction to reach a substantial audience and to be influential in the public sphere. The findings of this research provide a valuable reference for industry practitioners and researchers to deepen their understanding of the application of Twitter to green building construction, and the methods of using Twitter to promote important information related to sustainable construction.